Quality of Harvested Rainwater from a Green and a Bitumen Roof in an Air Polluted Region - Emil Tsanov; Dobril Valchev; Irina Ribarova; Galina Dimova (Salehan Institute of Higher Education, 2024)
A one-year study was conducted to evaluate the impact of air pollution and roof coating on runoff quality. An existing 440 sq meter bitumen roof of a single-story building was coated with an extensive green roof layer on one half. Rainfall and runoff samples from both roofs were collected during 11 rainfall events after the separation of the first flush. The study monitored several key parameters, including pH, electrical conductivity (EC), turbidity, chemical oxygen demand (COD), ammonium nitrogen, nitrate nitrogen, and phosphates. The study revealed that both types of roofs altered the rainfall quality, but the changes caused by the green roof were more substantial. Although the retention of runoff from green roofs has a widely acknowledged positive impact on collecting systems, our study shows that green roofs also result in a 7.5-fold increase in COD concentrations, a 5.4-fold increase in the sum of ammonium and nitrate nitrogen, and a 2.3-fold increase in phosphates compared to bitumen roofs. A clear link between the quality of rainwater/runoff and air pollution was not established. The study's findings will aid in the development and management of local rainwater harvesting systems and enhance global understanding of the primary quality parameters of various roof types, particularly in regions with air pollution. Doi: 10.28991/CEJ-2024-010-05-015 Full Text: PDF